Implementation of Data Science in Economics and Business - Palagan, Gilang Pandu (Manunggal Halim Jaya, 2025)
Digital business transformation and the 5.0 era of the industry have made data science develop rapidly, and it is much needed to capture the potential of big data as a basis for business decision-making. How the Faculty of Economics and Business integrates data science into the curriculum will be challenging, considering that data science requires an understanding of mathematics, statistics, and technology. This research attempts to define data science and design the integration of data science into economics and business. Through the literature review process, it can be understood that data science is a multidisciplinary science (Mathematics, statistics, and other sciences according to their respective fields). Based on this, integrating data science into economics and business can be carried out by designing a curriculum that considers conceptual aspects of theory and the technical continuity of the use of technology.